Amorphous Zn(O, Se) buffer layer for Cu(In, Ga)Se2 thin film solar cells. (September 2021) - Abdalla, Akram; Danilson, Mati; Oueslati, Souhaib; Pilvet, Maris; Bereznev, Sergei
Abstract: Amorphous Zn(O, Se) was used as a buffer layer with Cu(In, Ga)Se2 absorber in thin film solar cells. The complete device was fabricated using vacuum technique only, and no wet method was involved. The solar cells parameters were investigated with a change in the thickness of the buffer layer from 100 to 300 nm. In addition, the performance of the fabricated solar cells was compared to that of a reference solar cell, using CdS as a buffer layer on Cu(In, Ga)Se2 . The preliminary results of this Cd-free solar cells showed a reasonable device performance. Also, the parasitic absorption in the blue region for the Cu(In, Ga)Se2 /Zn(O, Se) device has been reduced, due to high transparency and high optical band gap of amorphous Zn(O, Se) buffer. Moreover, the Zn(O, Se) is relatively less toxic than the CdS buffer layer. Thus, the parasitic absorption in the 350–550 nm range and the toxicity raised from using CdS as a buffer layer have been overcome. Furthermore, open circuit voltage, short circuit current and an overall photoconversion efficiency of the device were enhanced to 454 mV and 27.1 mA/cm 2 and 5.0% respectively with decreasing the thickness of amorphous Zn(O, Se) buffer layer to 100 nm. Graphical abstract: Image 1 Highlights: For the first time, a novel Zn(O, Se) buffer layer applied with Cu(In, Ga)Se2 absorber. We emphasis that a complete device has been fabricated using vacuum technique only. A Cd-free Cu(In, Ga)Se2 /Zn(O, Se) solar cells showed a promising device performance. Optical losses of the Cu(In, Ga)Se2 /Zn(O, Se) cells in the blue region has been reduced. The device with 100 nm–thick of a-Zn(O, Se) showed the highest efficiency of 4.96%.